2013
DOI: 10.1121/1.4817878
|View full text |Cite
|
Sign up to set email alerts
|

Antisymmetric feature-guided ultrasonic waves in thin plates with small radius transverse bends from low-frequency symmetric axial excitation

Abstract: The influence of bends constituting annular polygonal structures on ultrasonic guided waves propagating along their axis is investigated. Considering a single bend as a bent plate connects this problem to the better-understood physics of guided waves in straight plates. Using a three-dimensional finite element simulation validated with experiments, bends in plates are shown to act as features that can concentrate and guide ultrasonic energy along their length. Two interesting feature-guided modes are identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 51 publications
4
22
0
Order By: Relevance
“…44 and 45). A competing mechanism for mode confinement due to velocity changes in flatter regions of eccentric pipes, similar to feature-guiding effects noted recently 39,46,47 is also revealed in a set of further studies considering more general pipe radius-thickness ratio and eccentricity cases. This paper is organized as follows.…”
Section: Introductionmentioning
confidence: 68%
“…44 and 45). A competing mechanism for mode confinement due to velocity changes in flatter regions of eccentric pipes, similar to feature-guiding effects noted recently 39,46,47 is also revealed in a set of further studies considering more general pipe radius-thickness ratio and eccentricity cases. This paper is organized as follows.…”
Section: Introductionmentioning
confidence: 68%
“…Such an effect is closely related to feature-guided wave phenomena noted in the literature in recent years. 3,7,8 Also an interesting observation is that pipe eccentricity does not seem to affect the T(0,1) mode as strongly, and its modal structure and nondispersive nature are very similar to the circular pipe even in cases of high ovalness. This paper is organized as follows.…”
Section: Introductionmentioning
confidence: 78%
“…3,7,8 Recent analytical studies (Postnova and Craster 11,12 ) have shown that curvature effects in waveguides are mathematically equivalent to local thinning. Again drawing upon the work of Postnova and Craster, 11,12 we find that for longitudinal modes, trapping is only possible for local thinning for Poisson ratio in the range of metals.…”
Section: Understanding the Physics Of Mode Focusing Based On Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The main challenge to the inspection of composites is the presence of multiple layers and anisotropic nature. Ultrasonic guided waves have been proven an attractive tool in inspection of large structures [2][3][4][5]. PZT and Fiber Bragg Gratings based sensors have been embedded often to monitor the crack growth during the curing process [6].…”
Section: Introductionmentioning
confidence: 99%